2021
DOI: 10.1007/s00205-021-01708-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-conservation of Dimension in Divergence-Free Solutions of Passive and Active Scalar Systems

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We refer to the articles by Caprino et al [6] for the two-dimensional case and by Crippa, Ligabue, Saffirio [12] for the threedimensional case. Finally, in connection with the study of singular velocities generated by singular measure-valued vorticities in fluid dynamics, we mention the recent work by Fefferman, Pooley and Rodrigo [20] on the construction of velocity fields for active scalar systems with measure-valued solutions whose support does not satisfy conservation of the Hausdorff dimension.…”
Section: The Resulting Velocity Fieldmentioning
confidence: 99%
“…We refer to the articles by Caprino et al [6] for the two-dimensional case and by Crippa, Ligabue, Saffirio [12] for the threedimensional case. Finally, in connection with the study of singular velocities generated by singular measure-valued vorticities in fluid dynamics, we mention the recent work by Fefferman, Pooley and Rodrigo [20] on the construction of velocity fields for active scalar systems with measure-valued solutions whose support does not satisfy conservation of the Hausdorff dimension.…”
Section: The Resulting Velocity Fieldmentioning
confidence: 99%
“…They constructed a divergence-free vector field u ∈ W 1,p (T d , R d ) with p < d − 1 and showed that the nonuniqueness of trajectories could occur on a set of positive measure. We also note that explicit examples of vector fields for which nonuniqueness happens on a set of full Hausdorff dimension but of measure zero are known [FPR21].…”
Section: Definition 13 (Regular Lagrangian Flow) a Map X Umentioning
confidence: 96%